Development and testing of Painometer: a Smartphone application to assess pain intensity. - De la Vega, Rocío; Roset, Roman; Castarlenas, Elena; Sánchez-Rodríguez, Elisabet; Solé, Ester; Miró, Jordi (American Pain Society, 2014)
Electronic and information technologies are increasingly being used to assess pain. This study aims to 1) introduce Painometer, a smartphone app that helps users to assess pain intensity, and 2) report on its usability (ie, user performance and satisfaction) and acceptability (ie, the willingness to use it) when it is made available to health care professionals and nonprofessionals. Painometer includes 4 well-known pain intensity scales: the Faces Pain Scale–Revised, the numerical rating scale–11, the Coloured Analogue Scale, and the visual analog scale. Scores reported with these scales, when used in their traditional format, have shown to be valid and reliable. The app was tested in a sample of 24 health care professionals and 30 nonprofessionals. Two iterative usability cycles were conducted with a qualitative usability testing approach and a semistructured interview. The participants had an average of 10 years’ experience in using computers. The domains measured were ease of use, errors in usage, most popular characteristics, suggested changes, and acceptability. Adding instructions and changing format and layout details solved the usability problems reported in cycle 1. No further problems were reported in cycle 2. Painometer has been found to be a useful, userfriendly app that may help to improve the accuracy of pain intensity assessment. Perspective: Painometer, a smartphone app to assess pain intensity, shows good usability and acceptability properties when used by health care professionals and nonprofessionals.
Es la versión preprint. https://openpolicyfinder.jisc.ac.uk/id/publication/14183
Keywords: Dolor; Aplicaciones informáticas - Desarrollo; Electrónica médica; Pain intensity; Assessment; mobile app; smartphone; usability testing